Kajian Tentang Konsep Jual Beli Dalam Perspektif Al-Qur’an Dan Hadist - Burhanuddin Robbani (ITB AAS INDONESIA Surakarta, 2023)
Buying and selling (business) is a daily activity carried out by humans in their lives. However, according to Islamic law, the practice of buying and selling has not been realized optimally by the Muslim community. There are even some of these Muslims who do not understand at all how to buy and sell that is correct according to Islamic law. The purpose of this study is to examine the concept of verses in the Qur'an and hadith regarding buying and selling. In this study, the authors used a qualitative descriptive writing method and used library research. The results of the research and the conclusions of this study are that as a perfect religion, Islam certainly has provided guidelines through the Al-Qur'an and Hadith so that humans carry out buying and selling procedures that are mutually beneficial and mutually acceptable to both parties. In essence, buying and selling transactions from the perspective of the Qur'an and Hadith must follow the example of the Prophet Muhammad, which is done honestly.